(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Education in general, and university education in particular, is subject to a number of problems, including administrative and organizational problems, which are reflected in the university’s output and results. And if a university administration like any administration is as constrained as a university administration, it has to stand there and try and deal with it. The problem of current research has emerged from the reality of the University Education Department at the University of Baghdad and the attempt to find solutions to it by setting future expectations for such education. The objective of the research is to identify the realities of university education and to arrive at a number of future expectations and perceptions of university and university institutions in Baghdad from the point of view of the departments in Baghdad. The researcher presented the theoretical aspect and previous studies, as well as the challenge to the research community, which consists of 171 department heads at the University of Baghdad for the academic year 2020-2021. Identifying a search sample of 41 department heads at 24%, the researcher relied on resolution as a search tool to answer his or her research objectives after conducting honesty and persistence. The researcher used the appropriate statistical means. After the application, the researcher analysed the results. The researcher came up with several findings, including that the reality of the university education department was at a level above the middle, closer to the good, and that the field of curriculum and student affairs came first. With scientific research and community service in fifth place, the researcher then set out a number of future expectations in the light of the order of the paragraphs on areas in terms of necessity and importance, and then came up with a number of conclusions and developed a set of recommendations and proposals for research.